On writing as technology, and technology as a miracle (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2021)
In the Peri Hermeneias, Aristotle suggests a certain continuity between writing and the structure of the human voice. Here, I propose such continuity between nature and what is deemed “technical” reveals a “miraculous” dimension of human activity.
Keywords: Aristoteles; Human voice; writting